Foliar Application of Nano-zinc and Iron Affects Physiological Attributes of Rosmarinus officinalis and Quietens NaCl Salinity Depression - Hassanpouraghdam, Mohammad Bagher; Mehrabani, Lamia Vojodi; Tzortzakis, Nikos G. (My University, 2020)
Salinity is an obstacle for plant growth and the exploitation of means like cation foliar to soften the negative effects is of interest. The impacts of NaCl salinity (0, 75, 150, and 225 mM) and nano-Zn and Fe foliar applications (0 and 3 mg L−1) were examined on yield and physiological characteristics of Rosmarinus officinalis grown in an open soilless culture system. Salinity decreased root growth and above-ground plant growth (fresh and dry weight), chlorophyll a and total chlorophyll content, and zinc accumulation. Nano-Fe and Zn foliar application had positive influence on the above-ground plant growth. The results showed that Zn2+ content was affected by the interaction between salinity and nano-Fe and Zn foliar application. The highest content of Zn2+ was found at no saline Zn-sprayed plants. The content of Zn2+, hydrogen peroxide (H2O2), malondialdehyde (MDA), and phenolics were affected by the independent effects of salinity or foliar application. Salinity increased the H2O2 and MDA content but nano-zinc and iron spraying alleviated salinity impacts and both H2O2 and MDA decreased. Nano-Fe and Zn foliar application increased total phenolics and total flavonoids content. Proline and chlorophyll a content, Na+, K+ amounts, and K+/Na+ ratio were affected by the salinity stress. Salinity decreased K+ content and K+/Na+ ratio but increased Na+ and proline content with more pronounced effects at 225 mM NaCl. Overall, foliar application of both elements improved the growth and salt tolerance of rosemary and their application would be advisable to the cultivation practices.
Keywords: Rosemary; Flavonoid; Malondialdehyde; Hydrogen peroxide; Proline; Saline